The Yo-Yo IR2 test: physiological response, reliability, and application to elite soccer - Krustrup, Peter; Mohr, Magni; Nybo, Lars; Jensen, Jack Majgaard; Nielsen, Jens Jung; Bangsbo, Jens (Medicine and science in sports and exercise, 2006)
To examine the physiological response, reliability, and validity of the Yo-Yo intermittent recovery level 2 test (Yo-Yo IR2). Thirteen normally trained male subjects carried out four Yo-Yo IR2 tests, an incremental treadmill test (ITT), and various sprint tests. Muscle biopsies and blood samples were obtained, and heart rate was measured before, during, and after the Yo-Yo IR2 test. Additionally, 119 Scandinavian elite soccer players carried out the Yo-Yo IR2 test on two to four occasions. Yo-Yo IR2 performance was 591 +/- 43 (320-920) m or 4.3 (2.6-7.9) min. Test-retest coefficient of variation in distance covered was 9.6% (N = 29). Heart rate (HR) at exhaustion was 191 +/- 3 bpm, or 98 +/- 1% HRmax. Muscle lactate was 41.7 +/- 5.4 and 68.5 +/- 7.6 mmol x kg(-1) d.w. at 85 and 100% of exhaustion time, respectively, with corresponding muscle CP values of 40.4 +/- 5.2 and 29.4 +/- 4.7 mmol x kg(-1) d.w. Peak blood lactate was 13.6 +/- 0.5 mM. Yo-Yo IR2 performance was correlated to ITT performance (r = 0.74, P < 0.05) and VO2max (r = 0.56, P < 0.05) but not to 30- and 50-m sprint performance. Yo-Yo IR2 performance was better (P < 0.05) for international elite soccer players than for moderate elite players (1059 +/- 35 vs 771 +/- 26 m) and better (P < 0.05) for central defenders (N = 21), fullbacks (N = 20), and midfielders (N = 48) than for goalkeepers (N = 6) and attackers (N = 24). Fifteen elite soccer players improved (P < 0.05) Yo-Yo IR2 performance by 42 +/- 8% during 8 wk of preseasonal training. This study demonstrates that the Yo-Yo IR2 test is reproducible and can be used to evaluate an athlete's ability to perform intense intermittent exercise with a high rate of aerobic and anaerobic energy turnover. Specifically, the Yo-Yo IR2 test was shown to be a sensitive tool to differentiate between intermittent exercise performance of soccer players in different seasonal periods and at different competitive levels and playing positions.